A message of hope for the world engulfed in hopelessness: an EATWOT perspective on the theology of hope - Dolamo, RTH (Nederduitse Gereformeerde Teologiese Tydskrif, 2003)
Some of the objectives of the General Assembly of the Ecumenical Association of ThirdWorld Theologians (EATWOT) held in Ecuador between September 24 and October 01, 2001 were to review the work of the organisation for the past twenty-five years of its existence, and to recommit itself to doing relevant theologies that would be responsive to the needs, aspirations, fears, and hopes of its regions. National liberation, socio-economic liberation, women liberation, and ecological liberation were some of the issues that were looked at. Challenges posed by globalisation, deepening poverty, killer diseases such as HIV/Aids, unabated brutalisation of women and children, escalating depletion of natural resources, degradation of creation, eruption of new conflicts and strife, and the general lack of democracy in some of EATWOT regions, were faced with courage as issues of divine imperative.